Pre-combustion capture of carbon dioxide in a fixed bed reactor using the clathrate hydrate process - Babu, Ponnivalavan; Kumar, Rajnish; Linga, Praveen (Energy, 2013)
Hydrate based gas separation (HBGS) process with silica sand and silica gel as contact medium was employed to capture CO2 from fuel gas mixture. Gas uptake measurement at three different pressures (7.5, 8.5 and 9.0 MPa) and 274.15 K were conducted for hydrate formation kinetics and overall conversion of water to hydrate, rate of hydrate formation were determined. Water conversion of up to 36% was achieved with silica sand bed compared to 13% conversion in the silica gel bed. Effect of driving force on the rate of hydrate formation and gas consumption was significant in silica sand bed whereas it was found to be insignificant in silica gel bed. Hydrate dissociation experiments by thermal stimulation (at constant pressure) alone and a combination of depressurization and thermal stimulation were carried out for complete recovery of the hydrated gas. A driving force of 23 K was found to be sufficient to recover all the hydrated gas within 1 h. This study indicates that silica sand can be an effective porous media for separation of CO2 from fuel gas when compared to silica gel. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate hydrates; Gas separation; Global warming; Pre-combustion